Fixed and dynamic bandwidth allocation strategies for wireless mobile integrated services networks - Mohamed, Nagla O.; Deniz, Dervis Z. (Springer, 2008)
Performance evaluation of two bandwidth allocation strategies in wireless mobile integrated services networks is carried out. Performances of the proposed strategies are compared with those of the traditional guard channels and threshold strategies. In the study, a single wireless cell which is accessed by voice and non-voice traffic types producing, respectively narrowband and wideband calls is considered. In the proposed strategies a number of channels are reserved in a fixed or dynamic fashion for the use of originating wideband calls in addition to the guard channels allocated for the handoff calls. The results indicate that the two strategies have comparable advantages and by manipulating the number of reserved channels, desired performance levels can be achieved. The dynamic reservation based strategy makes the system fairer for the originating wideband calls while maintaining low handoff dropping probability and acceptable channel utilization levels. On the other hand, the fixed reservation strategy provides a lower handoff call dropping at comparable channel utilization levels. The tradeoff is between improving the handoff call dropping versus the originating wideband call blocking. Both strategies provide better performance for the originating wideband calls compared with that provided by the traditional guard channels strategy.
Keywords: call admission control; handoff; bandwidth reservation; wireless mobile; guard channels